2020
DOI: 10.1142/s0192415x20500378
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: An Update on the Epidemiological, Clinical, Preventive and Therapeutic Evidence and Guidelines of Integrative Chinese–Western Medicine for the Management of 2019 Novel Coronavirus Disease

Abstract: As of 22 February 2020, more than 77662 cases of confirmed COVID-19 have been documented globally with over 2360 deaths. Common presentations of confirmed cases include fever, fatigue, dry cough, upper airway congestion, sputum production, shortness of breath, myalgia/arthralgia with lymphopenia, prolonged prothrombin time, elevated C-reactive protein, and elevated lactate dehydrogenase. The reported severe/critical case ratio is approximately 7-10% and median time to intensive care admission is 9.5-10.5 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
332
3
22

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(359 citation statements)
references
References 62 publications
(91 reference statements)
2
332
3
22
Order By: Relevance
“…At present, systemic glucocorticoids administration was empirically used for severe comp licat ions in order to suppress CS man ifestations in patients with COVID-19, such as ARDS, acute heart in juries, acute kidney complication, and patients with higher D-d imer levels, et al [3,23,24] However, there is no evidence from randomized clinical trials to support glucocorticoids treatment for COVID-19. Chen et al reported 19 (19%) patients were treated with glucocorticoids for 3-15 days (median 5 [3][4][5][6][7]), and methylprednisolone (1-2 mg/kg per day) are reco mmended for patients with ARDS, fo r as short a duration of treatment as possible [25].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…At present, systemic glucocorticoids administration was empirically used for severe comp licat ions in order to suppress CS man ifestations in patients with COVID-19, such as ARDS, acute heart in juries, acute kidney complication, and patients with higher D-d imer levels, et al [3,23,24] However, there is no evidence from randomized clinical trials to support glucocorticoids treatment for COVID-19. Chen et al reported 19 (19%) patients were treated with glucocorticoids for 3-15 days (median 5 [3][4][5][6][7]), and methylprednisolone (1-2 mg/kg per day) are reco mmended for patients with ARDS, fo r as short a duration of treatment as possible [25].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Mechanical ventilation may be necessary in cases of respiratory failure refractory to oxygen therapy, whereas hemodynamic support is essential for managing septic shock [37]. Different strategies can be used depending on the severity of the patient and local epidemiology [38,39]. Home management is appropriate for asymptomatic or paucisintomatic patients.…”
Section: Managementmentioning
confidence: 99%
“…Another nucleotide analog for the disruption of RdRp-dependent viral replication is favipiravir, which has investigational approval in several countries (128,129). Additional agents that are under study include emtricitabine/tenofovir and ribavirin (128,130).…”
Section: Nucleotide Analogs -Inhibitors Of Viral Genome Replicationmentioning
confidence: 99%